2017
DOI: 10.1093/ee/nvw166
|View full text |Cite
|
Sign up to set email alerts
|

Differential Host Plant-Associated Genetic Variation Between Sympatric Mite Species of the GenusOligonychus(Acari: Tetranychidae)

Abstract: Adaptation to different host plants can lead to host-associated differentiation (HAD). The mites Oligonychus perseae and Oligonychus punicae have a broad range of host plants, but, to date, records of them coexisting sympatrically had only been reported on avocado. However, our field observations showed both species coexisting on host plants other than avocado. The lack of previous records of these mites on the host plants studied here suggests only recent divergence to new host plant species. Previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…However, examination of their sequences (GenBank accessions KX072889-921; Guzmán-Valencia et al 2017) reveals levels of divergence between the COI of their avocado populations and those they sampled from the 2 Alnus species, similar to those reported herein (~8%), suggesting that they may also have encountered 2 cryptic species (in their case, on 2 different types of host plant). Unfortunately, the regions of COI used in our study and that of Guzmán-Valencia et al (2017) do not overlap, and additional genetic marker sequences are not available from Guzmán-Valencia et al (2017). Thus, it is uncertain whether or not there is overlap in the potential cryptic species reported in the 2 studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, examination of their sequences (GenBank accessions KX072889-921; Guzmán-Valencia et al 2017) reveals levels of divergence between the COI of their avocado populations and those they sampled from the 2 Alnus species, similar to those reported herein (~8%), suggesting that they may also have encountered 2 cryptic species (in their case, on 2 different types of host plant). Unfortunately, the regions of COI used in our study and that of Guzmán-Valencia et al (2017) do not overlap, and additional genetic marker sequences are not available from Guzmán-Valencia et al (2017). Thus, it is uncertain whether or not there is overlap in the potential cryptic species reported in the 2 studies.…”
Section: Discussionmentioning
confidence: 93%
“…Although we have strong molecular evidence for O. perseae being a complex of 3 cryptic species, biological (e.g., interpopulation mating studies) and ecological data (these putative cryptic species occupy near identical niches and cause very similar feeding damage) to sup-port their status is currently lacking, and we strongly recommend these as future lines of research. Interestingly, Guzmán-Valencia et al (2017) recently assessed genetic variation among sympatric O. perseae and O. punicae populations on 6 perennial host trees in the state of México, which included the hardwood species Salix bonplandiana Kunth (Salicaceae), Alnus jorullensis Kunth (Betulaceae), and Alnus acuminata Kunth (Betulaceae), alongside 3 avocado cultivars ('Hass', 'Fuerte', and 'Criollo'). As it relates to our study on avocado, Guzmán-Valencia et al (2017) found no genetic variation among the COI sequences of morphologically-identified O. perseae populations sampled from the 3 avocado cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation